التكامل الاقتصادي المغاربي وانعكاسه على الاقتصاد الليبي (Comprehensive Journal of Science, 2025)
This research aims to examine the importance of economic integration among the Maghreb countries (Libya, Tunisia, Algeria, Morocco, and Mauritania) in promoting economic development and utilizing shared economic potentials. The study focuses on the impact of this integration on the Libyan economy, particularly in terms of enhancing intra-regional trade, attracting investments, and strengthening economic stability. It also discusses the challenges hindering the achievement of this integration, such as economic and political differences among the Maghreb countries. Furthermore, the research seeks to propose recommendations for achieving effective economic integration that could enhance Libya's position in both the regional and global economy.
Keywords: Economic integration, Libyan economy, Intra-regional trade, Maghreb countries.